Answer:
The function f(x) = (x - 6)(x - 6) has only one x-intercept. But at (6, 0) not at (-6, 0).
Explanation:
The intercept form of a quadratic equation (parabola):
![y=a(x-p)(x-q)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lq0qj07kz6pwbx2kuzwc2154vqqv6g7krd.png)
p, q - x-intercepts
Therefore
The function f(x) = x(x - 6) = (x - 0)(x - 6) has two x-intercepts at (0, 0) and (6, 0)
The function f(x) = (x - 6)(x - 6) has only one x-intercept at (6, 0)
The function f(x) = (x + 6)(x - 6) = (x - (-6))(x - 6)
has two x-intercept at (-6, 0) and (6, 0)
The function f(x) = (x + 1)(x + 6) = (x - (-1))(x - (-6))
has two x-intercepts at (-1, 0) and (-6, 0).